FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN HEAT STRAIN PADA PEKERJA PABRIK TAHU DI KECAMATAN JELUTUNG - Diandri Saputra; Subakir Subakir; Abul Ainin Hapis (Jurnal Inovasi Penelitian, 2022)
Extreme environmental temperature is one of the physical factors in the work environment that has the potential to cause health problems for workers. Heat strain is a physiological response resulting from heat stress. The average temperature in the Tofu Factory production area in Jambi City is 29.6ºC, while the comfortable temperature for Indonesians is around 24-28ºC. The purpose of the study was to determine the factors associated with complaints of heat strain in tofu factory workers in Jambi City. The research design was cross sectional. The research sample is tofu factory workers in Jambi City as many as 30 workers. The sampling technique is total sampling. This research was conducted in August 2021. The research instrument was a questionnaire and a heat stress measurement tool. The data were analyzed using the Spearman test. As many as 66.7% of respondents experienced severe heat strain complaints, the average heat stress of the respondent's work environment was 29.6oC, 56.7% of respondents consumed less drinking water, 10.0% of respondents had an obese BMI and 6.7% of respondents had fat BMI. The results of the bivariate analysis showed that there was a relationship between heat stress (p=0.000), drinking water consumption (p=0.000) and complaints of heat strain from tofu factory workers. There was no relationship between BMI (p=0.457) with complaints of heat strain of tofu factory workers. It is expected that workers consume drinking water > 11 glasses and use clothes that can reflect heat such as wearing thin clothes, wearing loose-fitting shirts and easily absorbing sweat.